The Relationship between Stress Levels and the Performance of Nurses Caring for Covid-19 Patients at Private Hospital, Central Jakarta - Karina Songka; Stefanus Ides (MBUnivPress, 2022)
Covid-19 is a type of disease that is transmitted from one person to another through (droplets) when coughing or sneezing and the incubation period for COVID-19 is estimated to be between 1-14 days. The purpose of research are known the relationship between stress levels and the performance of nurses caring for Covid-19 patients at St Carolus Hospital, Central Jakarta. Descriptive correlation research with cross-sectional design was used. The sampling technique used purposive sampling and totaled 103 respondents. Data collected with questionnares using Google Forms. The results showed that the majority of respondents had severe stress levels (81.6%) and good performance (88.3%). The results of statistical analysis using Kendal Tau C showed there was no significant relationship between stress levels and nurse performance with p value (p = 0.597). Severe stress levels will affect the health of individuals physically, psychologically, socially and spiritually and have an impact on their performance. The suggestion for hospital can handle stress problems for nurses and maintain good nurse performance.